2018
DOI: 10.1016/j.cretres.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Integrated calcareous nannofossil and ammonite data from the upper Barremian–lower Albian of the northeastern Transdanubian Range (central Hungary): Stratigraphical implications and consequences for dating tectonic events

Abstract: The transition of post-obduction Neotethyan contraction to Eo-Alpine ("Austroalpine") nappe stacking that took place during the Early Cretaceous is an important event in the Cretaceous history of the Alpine-Carpathian-Dinaridic orogenic system. The Transdanubian Range (TR) in Hungary has been shown to have been impacted by both events. Dating of this transition has proved to be difficult; several interpretations were published during the last decades. Uniquely exposed in and around the Gerecse Mountains, the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…Cretaceous contractional structures show various trends (shortening directions) (Fig. 1b), which is traditionally explained by two or even three phases of folding and thrusting in the TR, well separated in time and in tectonic context (Tari, 1994;Csontos and Vörös, 2004;Csontos et al, 2005;Pocsai and Csontos, 2006;Palotai et al, 2006;Sasvári, 2008Sasvári, , 2009Tari and Horváth, 2010;Fodor et al, 2018;Szives et al, 2018). In contrast, our early results suggested that deviations of fold trends can be explained rather by inheritance of Triassic and Jurassic pre-orogenic normal faults than by multiphase folding (Héja et al, 2016(Héja et al, , 2017(Héja et al, , 2022.…”
Section: Central European Geologymentioning
confidence: 98%
See 1 more Smart Citation
“…Cretaceous contractional structures show various trends (shortening directions) (Fig. 1b), which is traditionally explained by two or even three phases of folding and thrusting in the TR, well separated in time and in tectonic context (Tari, 1994;Csontos and Vörös, 2004;Csontos et al, 2005;Pocsai and Csontos, 2006;Palotai et al, 2006;Sasvári, 2008Sasvári, , 2009Tari and Horváth, 2010;Fodor et al, 2018;Szives et al, 2018). In contrast, our early results suggested that deviations of fold trends can be explained rather by inheritance of Triassic and Jurassic pre-orogenic normal faults than by multiphase folding (Héja et al, 2016(Héja et al, , 2017(Héja et al, , 2022.…”
Section: Central European Geologymentioning
confidence: 98%
“…The Gerecse Hills (NE TR) represent an additional complexity, where even three different sets of folds and characteristic shortening directions seem to be present (Bada et al, 1996;Sasvári, 2008Sasvári, , 2009Fodor et al, 2018), namely folds or thrust with E-W, NE-SW and NW-SE strikes. Recently Fodor et al (2018) and Szives et al (2018) arranged the folding in a successive deformation story, and gave time constraints for two of them.…”
Section: Cretaceous -Early Miocene (?) Contractional Deformations -D3...mentioning
confidence: 99%
“…Tethyan late Barremian-Aptian standard stratigraphy and PF zonations of different authors. Correlation of ammonite and nannofossil zonations after Aguado et al 1999;Szives et al 2018 heating, magnetite becomes the only magnetic mineral left . The effect of Fe hydroxides, such as hydrogoethite (peak around 100-150 ºC on the second derivative), on thermomagnetic curves is negligible .…”
Section: Magnetostratigraphymentioning
confidence: 99%
“…A Vértessomlói Aleurolit kora alsó-középső-albai a biosztratigráfiai vizsgálatok alapján (Bodrogi 1993;Császár 1995;Császár 1998;Szinger 2008;Szives 2007;Szives et al 2018). A palinológiai vizsgálatok is ezt a kort támasztják alá (Juhász 1983).…”
Section: A Vértessomlói Aleurolit Formáció áLtalános Leírásaunclassified